Mechanistic Studies of Liquid Metal Anode SOFCs II: Development of a Coulometric Titration Technique to Aid Reactor Design. (2nd November 2016) - Toleuova, Aliya; Maskell, William C.; Yufit, Vladimir; Shearing, Paul R.; Brett, Daniel J.L.
Abstract: Improved understanding of the operation of liquid metal anode solid oxide fuel cells (LMA-SOFCs) is required to progress this promising energy conversion technology. In order to facilitate analysis and interpretation, initial studies have been carried out with a simple system in which hydrogen is used as the fuel and the liquid metal electrode is operated in a potential region where it effectively behaves as an 'inert' solvent for dissolved gases. A model for the processes taking place in a liquid tin anode (LTA) supplied with hydrogen has previously been reported which identified a key parameter, the Dynamic Oxygen Utilisation Coefficient, z ̅, important for understanding the operation and design of these systems. This parameter serves a similar role to the Damköhler number, widely applied in chemical reaction engineering to relate the chemical reaction rate to the transport phenomena rate. This paper describes the development of a method, named Anodic Injection Coulometry (AIC), to determine z ̅, together with an example of its application. Highlights: Analytical model of liquid anode solid oxide fuel cell presented. Dynamic Oxygen Utilisation Coefficient–design parameter with similar role to Damköhler number. Anodic Injection Coulometry used to determine Dynamic Oxygen Utilisation Coefficient.